Penggunaan Komik Digital Terhadap Membaca Pemahaman Literal Peserta Didik - Ayu Salsabila; Vevy Liansari (Jurnal Teknologi Pendidikan, 2024)
Research on the use of digital comics on students’ literal reading comprehension skills of fourth-grade elementary school students. The study was conducted using a quantitative method through a single-group design with pre- and post-treatment measurements, involving 30 students. Reading skills were measured using tests at the beginning and end of the study, and the differences in the results were analyzed using a paired t-test. The findings of the study showed a jump in the average score from 45.83 in the initial measurement to 85.00 after the use of digital comics, with a significance level of less than 0.05. Based on these results, it can be concluded that digital comics have a real impact on improving literal reading comprehension skills and have the potential to become a choice of Indonesian language learning media in elementary schools.